Perhitungan Harga Pokok Penjualan Pada Umkm Mie Ayam Bakso Nusantara - Rakhman, Arif; Maula, Kholida Atiyatul; Dewi, Marischa Aulia; Natalia, Anggi Amanda; Rani, Rani; Syahidah, Cinta Azzahara Ulla; Wahyudi, Adi Aris; Za'imuddin, Za'imuddin; Uliarta, Magdalena (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to analyze the calculation of the cost of goods sold (HPP) for Micro, Small and Medium Enterprises (MSMEs) "Nusantara Chicken Bakso Noodles". The research method used is a case study by collecting data through direct observation and interviews with business owners. Data analysis was carried out with a focus on the cost components involved in the production and sales process. The research results show that the calculation of COGS for the UMKM "Noodle Chicken Bakso Nusantara" involves various cost elements, including raw materials, labor, operational costs, and others. Apart from that, business owners also consider external factors such as market price fluctuations and customer demand in setting product selling prices. This research contributes to providing deeper insight regarding the COGS calculation strategy implemented by MSMEs in the culinary sector. It is hoped that the results can become a reference for similar MSMEs to improve operational efficiency and business sustainability in a competitive market.